2022
DOI: 10.1212/wnl.0000000000200851
|View full text |Cite
|
Sign up to set email alerts
|

APOE and Cerebral Small Vessel Disease Markers in Patients With Intracerebral Hemorrhage

Abstract: Background and Objective:We investigated the associations between Apolipoprotein E (APOE) genotype, intracerebral haemorrhage (ICH) and neuroimaging markers of cerebral amyloid angiopathy (CAA).Methods:We included patients from a prospective, multi-centre UK observational cohort study of patients with ICH and representative UK population controls. First, we assessed association of APOE genotype with ICH (compared to controls without ICH). Second, among patients with ICH, we assessed the association of APOE sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Along with previous recurrent ICHs, features associated with the highest risk of future CAA-related ICH include higher cerebral microbleed count, disseminated or multifocal cSS, and appearance of new cSS foci over time. 7,8 cSS appears to confer increased ICH risk even for patients with probable CAA without prior ICH, 9 underlining the importance of this marker for predicting future ICH.…”
Section: Stratification Of Ich Risk and Impact On Antithrombotic Trea...mentioning
confidence: 98%
See 1 more Smart Citation
“…Along with previous recurrent ICHs, features associated with the highest risk of future CAA-related ICH include higher cerebral microbleed count, disseminated or multifocal cSS, and appearance of new cSS foci over time. 7,8 cSS appears to confer increased ICH risk even for patients with probable CAA without prior ICH, 9 underlining the importance of this marker for predicting future ICH.…”
Section: Stratification Of Ich Risk and Impact On Antithrombotic Trea...mentioning
confidence: 98%
“…The risk of recurrent CAA-related ICH, estimated across studies in the range of 7.4% to 8.5% per year, 7,8 is the highest of all ICH types and indeed among the highest of any form of recurrent stroke. Along with previous recurrent ICHs, features associated with the highest risk of future CAA-related ICH include higher cerebral microbleed count, disseminated or multifocal cSS, and appearance of new cSS foci over time.…”
Section: Stratification Of Ich Risk and Impact On Antithrombotic Trea...mentioning
confidence: 99%
“…The Graz ICH cohort study has been described previously 14 ; in brief, it retrospectively identified all consecutive adult patients presenting to the University Hospital of Graz with firstever ICH, between 2008 and 2021, and collected all baseline data using standardized data collection sheets. Similar to the SIGNAL registry, neuroimaging with MRI was the standard of care for all patients unless contraindicated.…”
Section: Patient Selectionmentioning
confidence: 99%
“…We classified ICH as arteriolosclerosis in patients with a nonlobar ICH and relevant accompanying SVD (at least one of the following: ≥1 lacune; moderate or severe WMH; ≥1 deep (including brainstem) CMB; or severely ePVS in the basal ganglia [BGPVS] without lobar CMB or cSS); CAA when criteria for probable CAA based on the Boston 2.0 criteria 20 were fulfilled; mixed location SVD when there was a mixture of both lobar and deep signs of SVD; and cryptogenic in patients without any MRIvisible signs of SVD, as previously reported. 14 Cerebellar hemorrhages could be classified as any of the 4 neuroimaging phenotypes depending on the other imaging findings. Lobar ICH with SVD biomarkers but not meeting Boston 2.0 criteria was classified as mixed SVD.…”
Section: Neuroimaging Analysismentioning
confidence: 99%
“…In an additional study of white individuals from the UK presence of any APOE ε2 alleles was associated with all ICH (lobar and non-lobar) and with lobar ICH but not with deep only ICH. The APOE ε4 allele was associated with lobar ICH and with finger-like projects on head CT, a marker considered to represent probable CAA ( 83 ). However, ethnic and racial differences have been suggested in the relation of APOE genotype and ICH.…”
Section: Genetics Of Cerebral Small Vessel Diseasesmentioning
confidence: 99%